Ultrasound therapy in iliopsoas hematoma - Başak Bilir Kaya; Afitap İçağasıoğlu (İstanbul Kuzey Klinikleri, 2017)
Warfarin is an anticoagulant agent which is used frequently. One of its complications is life threatening bleeding which may lead to the termination of the therapy. Due to the widespread use of this therapy during the past few years, the incidences of its hemorrhagic complications have also increased significantly. In hemodynamically stable patients, it is possible to adopt conservative treatment strategies such as ultrasound (US) therapy. US is a physical therapy modality which is used widely in musculoskeletal disorders but there is little evidence about its effectiveness in hemorrhagic complications because of the limited amount of studies on this subject. A 77-year-old male who had been under oral anticoagulant therapy for 6.5 years applied to our clinic with complaint of severe thigh pain and numbness of anterolateral thigh. Ultrasonographic evaluation showed iliopsoas hematoma. US treatment, administered as a physical therapy modality, resulted in a faster resorption of the hematoma than expected. The patient fully recovered from clinically observed pain, meralgia paresthetica and reduced patellar reflex.